Congenital Hypogonadotrophic Hypogonadism: Minipuberty and the Case for Neonatal Diagnosis - Swee, Du Soon; Quinton, Richard (Frontiers in Endocrinology, 2019)
Congenital hypogonadotrophic hypogonadism (CHH) is a rare but important aetiology of pubertal failure and infertility, resulting from impaired gonadotrophin-releasing hormone secretion or action. Despite the availability of effective hormonal therapies, the majority of men with CHH experience unsatisfactory outcomes, including chronic psychosocial and reproductive sequelae. Early detection and timely interventions are crucial to address the gaps in medical care and improve the outlook for these patients. In this paper, we review the clinical implications of missing minipuberty in CHH and therapeutic strategies that can modify the course of disease, as well as explore a targeted approach to identifying affected male infants by integrating clinical and biochemical data in the early postnatal months.